2013
DOI: 10.1155/2013/210301
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Spinal Dysraphic Lesions

Abstract: Human tail and multiple spinal dysraphism are unusual congenital malformations. Human tail appeared as a prominent lesion from the lumbosacrococcygeal region, generally without connection between the tail and the neurospinal axis. Spinal dysraphisms are usually isolated, reaching 0.038% of incidence of multiple spinal dysraphisms in the same child. There were three cases described of unusual spinal dysraphic lesions: two cases of human tail and a case of a multiple thoracic myelomeningocele. The literature abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…We recommend, as suggested by other authors, that at least 400 µg of a folic acid supplement should be consumed daily; patients with an intermediate to high risk of neural tube defects (such as patients with a previous well-known history of neural tube defects) should consume 4-5 mg folic acid 5,22,23 . Investigation of proposed type of delivery revealed high rates (25%) of vaginal delivery.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…We recommend, as suggested by other authors, that at least 400 µg of a folic acid supplement should be consumed daily; patients with an intermediate to high risk of neural tube defects (such as patients with a previous well-known history of neural tube defects) should consume 4-5 mg folic acid 5,22,23 . Investigation of proposed type of delivery revealed high rates (25%) of vaginal delivery.…”
Section: Discussionmentioning
confidence: 86%
“…A previous study identified the irregularity and deficiency of prenatal monitoring in pregnant women, assisted by a poor public health system, in the state of Bahia (Brazil) 17 and indicated that these may be associated with the high incidence of spinal dysraphism 5,22,23 . We recommend, as suggested by other authors, that at least 400 µg of a folic acid supplement should be consumed daily; patients with an intermediate to high risk of neural tube defects (such as patients with a previous well-known history of neural tube defects) should consume 4-5 mg folic acid 5,22,23 .…”
Section: Discussionmentioning
confidence: 99%